2023
DOI: 10.1186/s12903-023-02729-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of argon plasma pre-treatment of healing abutments on peri-implant microbiome and soft tissue integration: a proof-of-concept randomized study

Abstract: Purpose Biofilm-free implant surface is ultimate prerequisite for successful soft and bone tissue integration. Objective of the study was to estimate the effects of argon plasma healing abutment pre-treatment (PT) on peri-implant soft-tissue phenotype (PiSP), inflammation, plaque accumulation and the microbiome (PiM) between non-treated (NPT) and treated (PT) abutments following 3-months healing period. The hypothesis was that cell-conductive and antimicrobial properties of PT would yield optim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 71 publications
3
13
0
Order By: Relevance
“…The present study showed that PT helped to reduce plaque accumulation and inflammation, in accordance with the study previously reported by this group. 28 Briefly, the previous study showed the same clinical results between the groups, while demonstrating that bacterial biofilms around PT were dominated by pioneer colonizers in contrast to NPT which was associated rather with late colonizers characteristic to mature biofilms. 28 This is important because infection, even in its sub-clinical grade, is considered the most devastating complication of biomaterials 46 due to its immediate interference with healing processes and far-reaching role in the development of future implant infections.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The present study showed that PT helped to reduce plaque accumulation and inflammation, in accordance with the study previously reported by this group. 28 Briefly, the previous study showed the same clinical results between the groups, while demonstrating that bacterial biofilms around PT were dominated by pioneer colonizers in contrast to NPT which was associated rather with late colonizers characteristic to mature biofilms. 28 This is important because infection, even in its sub-clinical grade, is considered the most devastating complication of biomaterials 46 due to its immediate interference with healing processes and far-reaching role in the development of future implant infections.…”
Section: Discussionmentioning
confidence: 63%
“…Sample size calculation was performed for the PI values estimated in the previous study with a similar design. 28 According to that, a total sample of 30 participants using α of 0.05 would result in a power of 0.8 with a drop-out of 25%. Demographic characteristics between the groups were analyzed using Fisher's exact test.…”
Section: Data Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…During the period that the gap between the implant surface and host bone is filled by bone ingrowth (osteogenesis), there is a probability of the microorganisms entering into this gap and adhering to the implant surface . This microbiota (bacteria, fungi) from the mucosal flora can induce the appearance of infections and consequent complications, , such as peri-implantitis. , Peri-implantitis is currently qualified as an emerging public health problem without an effective and predictive treatment …”
Section: Introductionmentioning
confidence: 99%
“…7,8 Peri-implantitis is currently qualified as an emerging public health problem without an effective and predictive treatment. 9 The initial biological response to a biomaterial is modulated by the immune system, 10 composed of macrophages. Macrophages play two crucial roles as they are responsible for inflammation and bone healing regulation 11 and avoid infection.…”
Section: Introductionmentioning
confidence: 99%